1971
DOI: 10.1111/j.1365-2389.1971.tb01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Euphrates Saline Soil in Lysimeters

Abstract: A saline soil from Euphrates alluvium at Abu-Ghraib was leached in two lysimeters with river water and the changes in composition of the soils and of the leachates were measured as well as the hydraulic conductivity. The results show that the presence of gypsum prevents the soils becoming sodic as leaching with irrigation water of favourable composition proceeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This may be the result of increased displacement of Na + due to an increased soil-solution of Ca +2 from amendments and subsequent leaching of the replaced Na 0 20 40 60 80 100 120 140 160 180 0 10 20 30 40 50 60 70 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 The results also showed that gypsum treatments required smaller quantities of water to remove Na + from soil compared with fresh and saline water treatments. Similar trends were reported for saline and saline-alkaline soils [11,29,32,33]. The leaching process at the beginning of the experiment showed the removal of salts from the easily percolated water in the macropores.…”
Section: Soil Leaching Experiment Desalinization Curvessupporting
confidence: 70%
“…This may be the result of increased displacement of Na + due to an increased soil-solution of Ca +2 from amendments and subsequent leaching of the replaced Na 0 20 40 60 80 100 120 140 160 180 0 10 20 30 40 50 60 70 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 The results also showed that gypsum treatments required smaller quantities of water to remove Na + from soil compared with fresh and saline water treatments. Similar trends were reported for saline and saline-alkaline soils [11,29,32,33]. The leaching process at the beginning of the experiment showed the removal of salts from the easily percolated water in the macropores.…”
Section: Soil Leaching Experiment Desalinization Curvessupporting
confidence: 70%